Digital Game Addiction and Lifestyle Behaviors in Turkish Adolescents - EROL, SAİME (MARMARA UNIV, INST HEALTH SCIENCES, 2021)
Objective: Digital game addiction is a concern that threatens public health around the world, especially in adolescents. This study was conducted to determine the relationship between digital game addiction and lifestyle behaviors in adolescents. Methods: The research was carried out in from three high schools offering different types of education in Maltepe district between March and April 2017. Data were collected by using the Introductory Information Form, Game Addiction Scale for Adolescents and Adolescent Lifestyle Profile Scale. Data were evaluated in computer environment. Descriptive data were shown with numbers, percentages and means. The relationship between game addiction and independent variables was evaluated by chi-square test, Mann-Whitney U test, Pearson Correlation Analysis and Logistic Regression Analysis. Results: 22.4% of adolescents were determined to be addicted to digital games. The mean scores of health responsibility, nutrition, interpersonal relationships and stress management of adolescents who had game addiction were significantly lower than the adolescents without game addiction. Digital game addiction rates were significantly higher in boys, vocational high school students, ninth grade students, and in those who described that their family had low income, that they had very poor relations with their families/friends, that they had very poor living conditions and that they were generally unhappy. Conclusions: It was determined that game addiction negatively affected adolescents' lifestyle behaviors, and there was a negative, low to moderately significant correlation between interpersonal relationships and stress management and game addiction.
Keywords: Digital game addiction; lifestyle behaviors; adolescents; INTERNET GAMING DISORDER; VIDEO GAMES; SOCIAL MEDIA; SCALE; VIOLENT; PLAY; VALIDATION; ATTITUDES; SYMPTOMS; VERSION